Implementation of Steganography on Voice Over Internet Protocol (VOIP) - Budi Santosa; Fandi Ahmad Juni Haryanto; Rifki Indra Perwira; Dessyanto Boedi Prasetyo (Institut Teknologi Dirgantara Adisutjipto, 2019)
Steganography is the science of hiding messages into a container without changes detected by the human senses. Cryptography is the science to keeping the message still safe. Combine between Steganography and cryptography can be used, but if there is exchange information still use separately, worry about there is a change in file size, which can result in damage. VoIP is a technology that allows to communicate with use communication lines on a network. VoIP refers more to voice communication. I am utilizing VoIP as a voice communication channel with voice as a medium for inserting secret messages. The research results that steganography techniques can be used with VoIP. By inserting a text message that is first encrypted and then entered into sound by the Least Significant Bit method. The test results, the Alpha testing, and Beta testing, resulted in a percentage above 90%.